LEGALITAS TINDAKAN DIREKSI PERSEROAN TERBATAS - Lismayanti, Erna; Purwaningsih, Endang; Yusuf, Chandra (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
The Board of Directors is the most important organ in a limited liability company, the Board of Directors as a company manager is appointed and terminated by the RUPS, the Board of Directors can represent the company both inside and outside the court. The expiry of the term of office of the Board of Directors has resulted in the legal actions that have been taken to become illegal and the Board of Directors no longer has the authority to represent the company. To validate all these legal actions must be approved by the RUPS and reappointed. The formulation of this problem is to find out the legality arrangements of the duties and authorities of the company's Directors in corporate actions and the legal consequences of the actions of the Directors of the company are limited in corporate actions after the end of their terms of office.The method used in this research is normative jurisdiction that applies statute approach and conceptual approach. The results showed that,  The Board of Directors has full responsibility in the activities of the company, the Board of Directors is captured legally and correctly if in carrying out management and representing the company based on the articles of association and the law, institutional and operational legality is a commitment that must be fulfilled by the company; and legal actions that have been taken by ex Directors are illegal, ex Directors can be prosecuted and subject to civil and criminal sanctions